Anatomical Pattern of Dorsal Metatarsal Arteries in a Black Kenyan Population - Amuti, Thomas; Oyugi, Lee; Ouko, Innocent; Ongidi, Ibsen; Ogeng'o, Julius (Journal of Morphological Sciences, 2019)
Introduction Knowledge of anatomical variations in the origin and in the course of the dorsal metatarsal arteries (DMTAs) is valuable for many procedures, including reconstructive surgeries and flap selection. However, there is a paucity of data on these arteries among black Africans.Materials and Methods The present study studied the origin and the location of DMTAs in 30 formalin-fixed cadaveric feet of adult black Kenyans at the Department of Human Anatomy of the University of Nairobi, Nairobi, Kenya.Results Dorsal metatarsal arteries were present in all of the cases. Of the right dorsalis pedis artery (DPA), in the majority of the cases, the 1st DMTA arose as the continuation of the DPA, while the 2nd to 4th DMTAs were given off as branches from the arcuate artery (AA). On the left feet, in the majority of the cases, the 1st DMTA arose as the continuation of the DPA, while the rest were given off as branches from the AA. In relation to the dorsal interossei muscles, all of the the arteries were either within the muscle fibers (53%) or beneath them (47%), on the right side. On the left side, the 1st DMTA was above the muscles in 40% of the cases; within the muscles in 53%; and beneath the muscles in 7%. The 2nd and 3rd DMTAs were above the muscles in 57% and in 53% of the cases, respectively.Conclusion These results reveal that the DMTAs show variation in their origin and position relative to the dorsal interossei muscles. These variations display bilateral asymmetry.
Keywords: dorsal metatarsal arteries; interossei muscles; dorsal myocutaneous flaps; foot; dorsalis pedis